2000
DOI: 10.1056/nejm200002243420802
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole to Prevent Preterm Delivery in Pregnant Women with Asymptomatic Bacterial Vaginosis

Abstract: The treatment of asymptomatic bacterial vaginosis in pregnant women does not reduce the occurrence of preterm delivery or other adverse perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
1
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(169 citation statements)
references
References 20 publications
2
157
1
9
Order By: Relevance
“…In brief, 3474 pregnant women, who were N18 years old and b14 gestational weeks, were consecutively recruited from May 2013 to September, when they came to Ma'anshan Maternal and Child Health Care Center for their first antenatal care visit. Gestational weeks were calculated using last menstrual period data, or estimated by ultrasound if their menstruation were irregular (Carey et al, 2000). At baseline (mean 10 gestational weeks), questionnaires and spot urine samples in the morning (8:00-10:00; within 7 days after completing questionnaires) were obtained.…”
Section: Study Participants and Samplingmentioning
confidence: 99%
“…In brief, 3474 pregnant women, who were N18 years old and b14 gestational weeks, were consecutively recruited from May 2013 to September, when they came to Ma'anshan Maternal and Child Health Care Center for their first antenatal care visit. Gestational weeks were calculated using last menstrual period data, or estimated by ultrasound if their menstruation were irregular (Carey et al, 2000). At baseline (mean 10 gestational weeks), questionnaires and spot urine samples in the morning (8:00-10:00; within 7 days after completing questionnaires) were obtained.…”
Section: Study Participants and Samplingmentioning
confidence: 99%
“…Les infections vaginales sont incriminées dans les avortements précoces [1][2][3] et tardifs ainsi que dans les accouchements prématurés et les endométrites du postpartum [2,4,5]. Dans le domaine de la reproduction, certaines bactéries comme chlamydia sont responsables de stérilités féminines par atteinte tubaire [6,7] et masculines par atteinte des canaux déférents [8].…”
Section: Introductionunclassified
“…The successful use of antibiotics for treatment to reduce the risk for adverse pregnancy outcomes in mothers with either BV or periodontal disease, yielded conflicting results 33,[177][178][179][180][181][182][183][184][185] and in fact, one study 185 demonstrated an increase in PTB following metronidazole administration.…”
mentioning
confidence: 99%